Blockchain as Electronic Evidence in the Indonesian Legal System: An Analysis of Legal Certainty in Crypto Asset Disputes - Olfriady Letunggamu; Rahmat Dwi Putranto (RADJA PUBLIKA, 2026)
This study examines the legal position and evidentiary value of blockchain-based records within the Indonesian legal system and their implications for legal certainty in crypto-asset disputes. Although Indonesian law recognizes electronic information and electronic documents as admissible evidence, the existing framework does not specifically regulate the authentication, verification, submission, and assessment of blockchain-based evidence in judicial proceedings. This study employs normative legal research using statutory, conceptual, comparative, and case approaches to analyze relevant legislation, legal doctrines, and court decisions concerning electronic evidence and crypto-asset disputes. The findings indicate that blockchain records possess strong technical characteristics of authenticity, integrity, traceability, and resistance to unauthorized alteration through cryptographic verification, timestamps, and distributed consensus. However, technical reliability does not automatically establish legal admissibility or evidentiary weight. In judicial practice, blockchain-based evidence may require supporting verification through digital forensic expertise, chain-of-custody documentation, and evidence linking blockchain addresses to the relevant legal subjects. The absence of specific procedural standards creates uncertainty in the authentication and assessment of blockchain evidence and may lead to inconsistent judicial treatment. This study proposes the development of specific judicial guidelines, particularly through a Supreme Court Regulation (PERMA), establishing standards for submission, authentication, technical verification, and judicial assessment of blockchain-based evidence. Such a framework would strengthen legal certainty while maintaining procedural fairness and compatibility with personal data protection requirements.